Cultural Dialectics With Catholic Education in The Border Areas in Sanggau Regency, West Kalimantan - Kristianus Kristianus; Magdalena Magdalena; Carolina Lala (IJECA (International Journal of Education and Curriculum Application), 2018)
This research is backed by the condition of the community located in the border area of Indonesia-Malaysia especially in Entikong subdistrict of Sanggau Regency. As the frontier area of social and cultural life of community education in this region has always been a concern especially in conjunction with Malaysian Sarawak.  The inhabitants of this region generally embraced Catholicism and Catholic missionaries establishing schools of KINDERGARTEN to high school which are equipped with dormitories. The problem in this study is how the Catholic religious education influences the dialectics of Dayak culture in the region. Data taken using qualitative method is by observation, interviews and living with the community there. The study was held in July-September 2018. The results concluded that the education developed by Catholic missionaries has an effect on the dialectics of Dayak culture in this area. Besides education, other factors also affect the history, politics, and daily life at the border.  Another conclusion is that the Catholic missionary (the work of the education that has been developed) has an effect on the identity of Dayak culture in this region, Dayaks are more confident. This could be so because Catholic missionaries appreciate Dayak culture.  It is clear that the education developed by the Catholic religion plays a role in the formation of basic and primary materials for the formation of Dayak cultural dialectics in Entikong and other border areas in West Kalimantan.